Drug innovation via integration of traditional Chinese and Western medicine - Zhineng Li; Le Yang; Ling Kong; Hui Sun; Ye Sun; Xiangmei Chen; Fengting Yin; Guangli Yan; Xijun Wang (Science of Traditional Chinese Medicine)
Abstract. Innovative drugs are defined as new chemical entities that play a vital role in the treatment and maintenance of human health. While single-target innovative drugs have achieved notable success, they face limitations in addressing the increasingly complex and precise spectra of diseases. The advent of multi-target innovative drugs offers new opportunities, supported by a growing body of pharmacological evidence. Herbal medicines are recognized as valuable sources of multi-target therapeutics due to their proven efficacy in treating complex diseases. However, the identification and validation of such drugs from herbal sources continue to pose significant challenges. This paper presents a comprehensive review of the literature on traditional Chinese medicine, integrated medicine, chemistry, and biology from 2015 to 2025. It summarizes the strategies employed in integrating traditional Chinese and Western medicine for innovative drug development, along with successful application cases. We believe these efforts will deepen understanding of the current landscape, accelerate the discovery of multi-target innovative drugs from herbal medicine, and contribute to addressing major human health challenges.